Cuora amboinensis Roaming Patterns in Artificial Habitats in The Ex-Situ Turtle Conservation Area, Bengkulu University - Haryono, M.; Karyadi, Bhakti; Parlindungan, Deni; Sutarno, Sutarno; Ruyani, Aceng; Dewi, Novi Ratna (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
This research was carried out in September-October 2023 at the Bengkulu University ex-situ turtle conservation area, aiming to provide comprehensive knowledge about roaming patterns, active times, and movement areas in artificial habitats so that they can be used to develop effective conservation strategies for maintaining the preservation of C. amboinensis in the ex-situ turtle conservation area, Bengkulu University. This study observed 11 individual turtles (4 females and 7 males). This research uses literature study methods and direct observations in the field. The results obtained showed that C. amboinensis had: high mobility because all artificial areas were explored. The active time of C. amboinensis is in the morning and evening. The range of movement of males is greater than that of females. Mounting activity occurs spontaneously or directly when male C. amboinensis and female C. amboinensis meet in a certain area. The roaming pattern of C. amboinensis occurs randomly and the range of movement between male and female C. amboinensis is very different.